The Influence Of Digital Marketing Literacy On Digital Marketing Adoption Of Pangkalpinang MSME Actors - Chairunnisa Tri Meidita; Asep Suryana; Kunto Adi Wibowo (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research uses a survey method that will explain a trend, attitude, or opinion of the population that will be described quantitatively and test the relationship of several variables. Seeing the phenomenon related to digitalization faced by MSME, this study aims to measure the level of digital marketing literacy of MSME towards digital marketing adoption through perceived benefits, perceived ease of use, and intention to use digital marketing. The target population of this research is MSME in Pangkalpinang City who have participated in digital marketing training. This study will use path analysis to test the hypothesis and determine the amount of influence of the independent variable on the dependent variable. The results show that overall digital marketing literacy does not have a significant influence on digital marketing adoption through perceived benefits, ease of use and intention to use digital marketing.